Ruptured Ectopic Pregnancy in Caesarean Section Scar: A Case Report - Kamal Singh; Anjali Soni; Shelly Rana (Hindawi Limited, 2012)
Pregnancy implantation within previous caesarean scar is one of the rarest locations for an ectopic pregnancy. Incidence of caesarean section is increasing worldwide and with more liberal use of transvaginal sonography, more cases of caesarean scar pregnancy are being diagnosed in early pregnancy thus allowing preservation of uterus and fertility. However, a delay in either diagnosis or treatment can lead to uterine rupture, hysterectomy, and significant maternal morbidity. We are reporting a rare case of first trimester caesarean scar pregnancy with viable fetus in the process of rupture, where uterine repair could be done, thus preserving the future fertility.